UR_GERICHTE 2017_OG SP 17 vom 29. Mai 2017 - UR Obergericht (2017)
1. Strafprozessordnung. Art. 221 Abs. 1 lit. a, Art. 224 Abs. 2, Art. 226 Abs. 1, Art. 232, Art. 237 Abs. 2 lit. b, c, d, Art. 237 Abs. 4 StPO. Sicherheitshaft. Zuständigkeit. Verfahren. Anordnung von Ersatzmassnahmen.